Delineation of two intracranial areas and the perpendicular intracranial width is sufficient for intracranial volume estimation - Niklas Klasson (Insights into Imaging, 2018)
Abstract Objectives The aim of the present study is to determine if the delineation of one or two optimally chosen intracranial areas (ICA) is enough to achieve adequate estimates of intracranial volume (ICV) in magnetic resonance imaging. Methods The correlations of 62 fully delineated ICVs with four types of ICV estimates were calculated. The estimate types were: (1) a single midsagittal ICA, (2) single ICA multiplied by the intracranial width perpendicular to the ICA, (3) sum of two ICAs multiplied by the perpendicular intracranial width and (4) shape-preserving piecewise cubic interpolation using two ICAs. For methods 2–4, the fully delineated ICVs were randomly separated into an evaluation and a validation set of equal size. Method 1 was validated against all of the fully delineated ICVs. Results Estimates from method 1 had a Pearson correlation of 0.904 with fully delineated ICV. For method 2, the correlation was 0.986 when delineating the sagittal ICA at 31% of the sagittal intracranial width. For methods 3 and 4, the correlations were both 0.997 when delineating the sagittal ICAs at 17.5 and 64% and at 12 and 64% respectively. Conclusions Delineation of two specific intracranial areas is sufficient for intracranial volume estimation. Main messages • Delineation of two specific intracranial areas is sufficient for intracranial volume estimation. • The estimates had a Pearson correlation of 0.997 with intracranial volume. • The estimation should take no more than 5 min.